CEFDA: common exchange format for development activity information - Di Lauro, Anne (IDRC OttawaCA, 1992)
Provides a common record format for use in the effective exchange of computerized information among donor agencies. CEFDA is being used by organizations contributing data to the DAI CD-ROM (Development Activity Information on CD-ROM).